Base Salaries, Bonus Payments, and Work Absence among Managers in a German Company - Pfeifer, Christian (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Questions about compensation structures and incentive effects of pay-for-performance components are important for firms' Human Resource Management as well as for economics in general and labor economics in particular. This paper provides scarce insider econometric evidence on the structure and the incentive effects of fixed base salaries, paid bonuses, and agreed bonuses under a Management-by-Objectives (MBO) incentive scheme. Six years of personnel data of 177 managers in a German company are analyzed. The main findings are: (1) base salaries increase significantly with age, whereas bonuses decrease with age; (2) larger agreed bonuses are correlated with fewer absent working days.
Keywords: Absenteeism; Incentive; Insider Econometric; Wage; 330 Wirtschaft